Influencia de estabilizantes goma guar y goma xathan en la calidad físico-química organoléctica del néctar de tamarindo(Tamarindus indica l.) - Ávila Mora, Fabián Fabricio (2016)
Aim of this research was to evaluate the influence of two kinds of stabilizers in the elaboration of a nectar of tamarindo on the ESPAM - MFL (Escuela Superior Politécnica Agropecuaria de Manabí – Manuel Félix López) was drawn up the nectar with raw tamarind with a dilution of 1-10, which includes 1 kg of pulp in 10 litres of water as the standard INEN 2337 for fruit nectar nectar evaluated parameters (pH, acidity, density, viscosity) physicochemical of INEN 2337 standard 2008 to Nectars and fruit juices. The following organoleptic variables (smell, taste, color, and general appearance) were evaluated. Two best treatments were obtained in the investigation, which according to the statistical analysis corresponded to the treatments A1B2 and A1B3 representing the stabilizer gum xanthan gum to 2% and 3% respectively, reflected in the stability and viscosity, relevant parameters in this research; This research revealed significant differences between their two best treatments, with the exception of the stability that showed high significance. Concerning organoleptic variables determined by mean sof an affective test using a five-point hedonic scale test, comparing the best treatments such as A1B2 and A1B3 against a witness which did not contain any rubber showing favorable results in the investigation.